2018
DOI: 10.1007/s00167-018-5044-x
|View full text |Cite
|
Sign up to set email alerts
|

Return to sport after acute acromioclavicular stabilization: a randomized control of double-suture-button system versus clavicular hook plate compared to uninjured shoulder sport athletes

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 37 publications
(60 reference statements)
0
31
0
Order By: Relevance
“…Overhead athletes needed to change sport activity significantly more often (54% vs 12%; p = 0.011) and 27% had to reduce their sports level to low-demanding sports, while none of the non-overhead athletes lowered their level ( p = 0.029). Muller et al [24] found that overhead athletes had more benefit from a double-suture-button technique than collision athletes and suggested non-anatomic clavicle hookplate as a good alternative for the collision athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overhead athletes needed to change sport activity significantly more often (54% vs 12%; p = 0.011) and 27% had to reduce their sports level to low-demanding sports, while none of the non-overhead athletes lowered their level ( p = 0.029). Muller et al [24] found that overhead athletes had more benefit from a double-suture-button technique than collision athletes and suggested non-anatomic clavicle hookplate as a good alternative for the collision athletes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of Gowd et al [7] showed, although there is a trend toward minimally invasive procedures, there are no differences in loss of reduction, complication rate and revision rate between open and arthroscopic AC joint reconstruction. Considering return to sport outcomes, the RCT by Muller et al [24] showed that patients treated arthroscopically by double cortical buttons had a superior level of performance in shoulder sport, close to the level of performance in healthy athletes, compared to patients treated by a hookplate.…”
Section: Discussionmentioning
confidence: 99%
“… 13 and Müller et al. 24 evaluated the rate of return to play following AC joint stabilization and found the arthroscopic SB enabled greater sport-specific outcomes and an ability to return at a greater level. A recent systematic review by Kay et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bajnar et al also highlighted this tendency [27]. Recent literature also shows that patients treated with double suture button reconstruction were much more likely to return to previous sport activity levels compared to patients treated with hook plating [28].…”
Section: Discussionmentioning
confidence: 99%